2001
DOI: 10.1063/1.1398578
|View full text |Cite
|
Sign up to set email alerts
|

Electric dipole polarizabilities of Ni12–58

Abstract: Articles you may be interested inSite-specific analysis of dipole polarizabilities of heterogeneous systems: Iron-doped Si n (n = 1-14) clusters J. Chem. Phys. 138, 094304 (2013); 10.1063/1.4793276 Thermally induced polarizabilities and dipole moments of small tin clustersThe electric dipole polarizabilities of Ni 12 -Ni 58 have been measured via a molecular beam deflection experiment. The majority of the clusters display polarizabilities ␣ between 4 and 6 Å 3 per atom, below the atomic value of 6.8 Å 3 and ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 41 publications
0
29
0
Order By: Relevance
“…In contrast to the electric deflections of normal clusters, [13][14][15] the deflections of niobium clusters at low temperatures show several anomalies. In particular (i) the maximum deflection is linearly proportional to the applied electric field; (ii) the deflected beam profiles are asymmetric; (iii) at higher temperatures the spontaneous dipoles vanish and the deflections are due to the polarizability of the cluster.…”
Section: Introductionmentioning
confidence: 86%
“…In contrast to the electric deflections of normal clusters, [13][14][15] the deflections of niobium clusters at low temperatures show several anomalies. In particular (i) the maximum deflection is linearly proportional to the applied electric field; (ii) the deflected beam profiles are asymmetric; (iii) at higher temperatures the spontaneous dipoles vanish and the deflections are due to the polarizability of the cluster.…”
Section: Introductionmentioning
confidence: 86%
“…1 It has also revealed that small rhodium clusters are ferromagnetic with magnetic moments per atom of as much as 0.8 Bohr magnetons ͑ B ͒, 2 while bulk rhodium is paramagnetic. Manganese clusters were found to be ferromagnetic or ferrimagnetically ordered in the size range from Mn 5 to Mn 99 , 3,4 with magnetic moments per atom in the range 0.3-1 B .…”
Section: Introductionmentioning
confidence: 98%
“…Of the experimental studies on Ni N clusters, 29,30,31,32,33,34,35,36,37 the chemical-probe experiments 29,30,31,32,33,34,35,36 have given very valuable information on the structure of the smaller clusters. On the other hand, results for medium and large Ni clusters, 37 obtained by performing near-threshold photoionization and time-of-flight mass spectroscopy can be used in identifying particularly stable clusters and, subsequently, in providing information on growth modes.…”
Section: Introductionmentioning
confidence: 99%